Manajemen Strategi Pengelolaan Data Siswa Berbasis Web di SMA Negeri 1 Pangandaran - Deti Kurnia; Tatin Suhertin; Anna Vanista; Yayat Hidayat (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
Currently technology is developing very rapidly, especially in the field of education. The presence of a management information system really helps schools in managing student data, facilities and infrastructure, educators and education staff. The author's aim in writing this journal is to find out the management of student data management from planning, organizing, implementing, controlling as well as obstacles and strategies in managing student data at SM N 1 Pangandaran. In this journal we can find out that effective and efficient student data management is important in schools because it can make it easier for those who manage the data and the results. Based on these conditions, SMA N 1 Pangandaran school handled this problem by creating a website for effective and efficient management of student data. The method used in this research is using a qualitative descriptive approach. The technique in this research is the method of observation, interviews and documentation related to information systems as a means of managing student data at SMA N 1 PANGANDARAN. The object of this research is to analyze the planning, organization, implementation and control of the use of the website in managing student data at SMA N 1 PANGANDARAN. The results of the research show that there is a student data management manager who uses the school website based on the vision, mission and objectives, which is very effective and systematic. Managing student and teacher data is easier because it is automatically managed by the website. This implementation has had a significant impact on the student data management process.